Forest Hydrology and Watershed - Meng, Fan-Rui (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Hydrological processes in forested watersheds are influenced by environmental, physiological, and biometric factors such as precipitation, radiation, temperature, species type, leaf area, and extent and structure of forest ecosystems. Over the past two centuries, forest coverage and forest structures have been impacted globally by anthropogenic activities, for example, forest harvesting, and conversion of forested landscapes for plantations and urbanization. In addition, since the industrial revolution, climate change has resulted in profound impacts on forest ecosystems due to higher carbon dioxide (CO2) concentration or CO2 fertilization, warmer temperatures, changes in frequency and intensity of extreme weather events and natural disturbances. As a result, hydrological processes in forested watersheds have been altered by these natural and anthropogenic factors and these changes are expected to accelerate due to future changing climatic conditions.